Public Relations & Impression Management - Farikha Rachmawati (Kanal: Jurnal Ilmu Komunikasi, 2022)
Fashion can be used as a medium of communication and a strategy for public relations to make an impression. This study aims to analyze the public relations strategy in performing impression management to stakeholders through fashion. Public relations practitioners in Indonesia tend to use fashion as one of the main factors to get a good initial impression from stakeholders. The method used in this study is a qualitative method to explore the fashion used by public relations practitioners. Through data collection techniques, namely interviews and documentation, the research was conducted on 15 public relations practitioners in Indonesia using convenient sampling technique. Furthermore, through data analysis techniques Miles, Hubberman, and Saldana researchers conducted data analysis and then tested by triangulation. The results of this study indicate that impression management through fashion is effective in increasing the positive image of stakeholders for public relations practitioners. Indonesian public relations practitioners tend to use the impression management strategy of ingratiation through fashion to get public attention. In addition, the research findings show that fashion is used to represent a positive image of the organization and facilitate communication practices. The research findings show that the influence of fashion is not only on the front stage but also contributes to success not only in physical fashion, but more on internal appearance, namely confidence, honesty, being a good listener and open minded. Moreover, good impression management is considered to affect the success of communication.